1979
DOI: 10.1103/physrevlett.42.1031
|View full text |Cite
|
Sign up to set email alerts
|

Nucleon-Number Dependence of Inclusive Dihadron Production in Proton-Nucleus Collisions at 400 GeV/c

Abstract: PHYSICAL REVIEW LETTERS 16APRIL1979nals was estimated from single-particle inclusive data in which one arm was used as the trigger, and the other (untriggered) arm recorded the relative frequency of Cherenkov signals. 4 The original configuration of the apparatus is described by Bintinger et al. (Ref. 2), and the rearranged configuration (for which one of the Cherenkov counters was relocated behind the magnet) is described in Ditzler et al. (Ref. 2).Several unexpected results have recently raised interest in h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

1979
1979
1993
1993

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…3 we plot a for h+h~ pairs (without regard to particle type) versus mass, in comparison to data from Ref. 4,Finley et al, 12 and a recent experiment by Abramov et al u All data shown, with the exception of those from Ref. 12, are consistent with a=l for hadron pairs (summed over net p T ).…”
Section: A Dependence Of the Inclusive Production Of Hadrons With Higmentioning
confidence: 68%
“…3 we plot a for h+h~ pairs (without regard to particle type) versus mass, in comparison to data from Ref. 4,Finley et al, 12 and a recent experiment by Abramov et al u All data shown, with the exception of those from Ref. 12, are consistent with a=l for hadron pairs (summed over net p T ).…”
Section: A Dependence Of the Inclusive Production Of Hadrons With Higmentioning
confidence: 68%
“…We take the nucleus to be a ,t A similar behaviour has been observed in the production of hadron pairs [12,13]. ,2 We should mention that one also observes large Valuesof n for a proton trigger.…”
Section: F Dzn 70 Gn -I Nmentioning
confidence: 83%
“…In the remainder of this Letter, we describe some of those consequences and their implications for the analysis of experimental data. The issues are of particular importance for dihadron data, because there is a large body of published data [8][9][10][11][12] of high statistical accuracy whose interpretation may become clearer when nuclear kr effects are taken into account in the analyses.…”
Section: Nuclear Rescattering Effects In Massive Dihadron Productionmentioning
confidence: 99%
“…In the remainder of this Letter, we describe some of those consequences and their implications for the analysis of experimental data. The issues are of particular importance for dihadron data, because there is a large body of published data [8-12] of high statistical accuracy whose interpretation may become clearer when nuclear kr effects are taken into account in the analyses.Several experiments [8][9][10][11][12] have measured the A dependence of a differential cross section for the process pA -• dihadrons for proton beams of momenta > 400 GeV/c. The A dependence is usually parametrized as A a , where a > 1 is called an anomalous nuclear enhancement; a < 1 is called shadowing, and a = 1 would be expected for independent hard scattering from each of the nucleons.…”
mentioning
confidence: 99%
See 1 more Smart Citation